Tuberculoma of the liver - Bharathi A; Nagarjuna K; Prasad GVSN; Reddy J; Ravi Prasad D (Wolters Kluwer Medknow Publications, 2008)
We report an isolated giant solid macronodular tuberculoma in an 8-year-old boy. A large-space-occupying lesion in the right lobe with nodular surface and hard consistency mimicked liver malignancy. This case is unusual as the ultrasonography, computed tomography scan, and aspiration cytology were all suggestive of a malignant tumor. Laparotomy confirmed a 15 x 10 cm nodular tumor present in the right lobe of liver. The segments 5, 6, 7, and 8 were excised. The histopathology revealed tuberculosis.